2021
DOI: 10.1021/acs.joc.1c02501
|View full text |Cite
|
Sign up to set email alerts
|

Dieckmann Condensation of Ugi N-Acylamino Amide Product: Facile Access to Functionalized 2,2-Disubstituted Indolin-3-ones

Abstract: Structurally unique 2,2-disubstituted indolin-3-ones with a quaternary carbon center have been constructed through a novel C–C bond formation at the C3 position of Ugi N-acylamino amide adducts employing an organic base-mediated Dieckmann condensation. This facile, flexible protocol can be fine-tuned to construct drug-like pyrazino­[1,2-a]­indole fragments with the same quaternary carbon center only through the variation of the acid part in Ugi input. This novel and expeditious methodology has a broad scope an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…Our research group previously designed and synthesised a series of compounds targeting tubulin, and found that these compounds were able to exert significant inhibitory activity against hepatocellular carcinoma cells [ 10 ]. In order to evaluate the therapeutic potential of these derivatives in CRC cells, an MTT assay was employed to assess their cytotoxicity in HCT116 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group previously designed and synthesised a series of compounds targeting tubulin, and found that these compounds were able to exert significant inhibitory activity against hepatocellular carcinoma cells [ 10 ]. In order to evaluate the therapeutic potential of these derivatives in CRC cells, an MTT assay was employed to assess their cytotoxicity in HCT116 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given that these compounds targeting tubulin were designed and synthesised in our previous study [ 10 ], we considered whether DHPITO was a bona fide inhibitor of tubulin. As anticipated, morphological observations revealed that the HCT116, HCT8, and SW480 cells grew in round grapelike clusters following DHPITO treatment, and these morphological changes were very similar to those observed in cells treated with paclitaxel, which is a microtubule depolymerisation inhibitor that binds to the tubulin polymer ( Figure 2 A and Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the cyclization reactions from acyclic starting materials provide a step-economical strategy for the construction of 2,2-disubstituted indolin-3-ones. 6 α-Oxo metal carbenes represent a highly versatile intermediate in organic synthesis. 7 Recently, much attention has been paid to the annulation reactions initiated by the generation of α-oxo metal carbenes from readily available acyclic o -nitroalkynes.…”
mentioning
confidence: 99%
“…1). 1 Much attention has been paid to the development of efficient strategies for constructing 2,2-disubstituted indolin-3-ones, among which oxidative rearrangement of 2,3-disubstituted indoles, 2 cyclization reactions from acyclic starting materials, 3 and the direct conversion reaction of 3 H -indol-3-ones or indolin-3-ones 4 represent the classic synthetic routes. Nevertheless, these strategies mainly require transition-metal catalyst or multistep synthesis of starting materials.…”
mentioning
confidence: 99%